Recovery of the injured neural system through gene delivery to surviving neurons in Parkinson’s disease - Chanchal Sharma; Sehwan Kim; Hyemi Eo; Sang Ryong Kim (Neural Regeneration Research)
A critical unaddressed problem in Parkinson’s disease is the lack of therapy that slows or hampers neurodegeneration. While medications effectively manage symptoms, they offer no long-term benefit because they fail to address the underlying neuronal loss. This highlights that the elusive goals of halting progression and restoring damaged neurons limit the long-term impact of current approaches. Recent clinical trials using gene therapy have demonstrated the safety of various vector delivery systems, dosages, and transgenes expressed in the central nervous system, signifying tangible and substantial progress in applying gene therapy as a promising Parkinson’s disease treatment. Intriguingly, at diagnosis, many dopamine neurons remain in the substantia nigra, offering a potential window for recovery and survival. We propose that modulating these surviving dopamine neurons and axons in the substantia nigra and striatum using gene therapy offers a potentially more impactful therapeutic approach for future research. Moreover, innovative gene therapies that focus on preserving the remaining elements may have significant potential for enhancing long-term outcomes and the quality of life for patients with Parkinson’s disease. In this review, we provide a perspective on how gene therapy can protect vulnerable elements in the substantia nigra and striatum, offering a novel approach to addressing Parkinson’s disease at its core.